Are We All Refugees?. Issue 2 (17th February 2021) - Togashi, Koichi; Brothers, Doris
ABSTRACT: This article examines the refugee experience as a loss of home. When home is viewed as much more than simply a place but is understood as a concept that signifies how human beings locate themselves among other human beings in the world, the loss of home is seen as almost always traumatic. The article begins with the psychoanalytic literature on the refugee experience. Then with reference to a study of the refugees of the Fukushima earthquake, tsunami and nuclear reactor explosions, it discusses the societal traumas that drive people out of their homes. It is suggested that all humans share a sense of radical anxiety upon being disconnected from or unstably bonded to home. Next, Buber's understanding of home is considered. The article concludes with an illustrative clinical vignette and a discussion of the possible intergenerational transmission of exile and homelessness starting with the experience of early humans.